Economic analysis of broiler production in Peninsular Malaysia - Abdurofi, Ilmas; Ismail, Mohd Mansor; Abdul Wahab, Kamal Hisyam; Gabdo, Bashir Hamman (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The domestic demand for broiler meat is one of the highest in the Malaysian markets. The industry requires continuous evaluation to identify the existing problems and improves its competitive advantage. Thus, economic analysis of this sort will continue to update current statistics on production cost, output and profitability. Following this, the study, therefore, aims to assess the existing financial condition of farmers, marginal cost of production, total net income and input-output ratio of broiler production in different regions in Peninsular Malaysia. The study used multi-stage sampling in selecting 310 operators from Southern, Northern, East Coast and Centeral regions. The analytical tools include descriptive statistics and farm budget. The findings disclosed that the broiler farm incurs major cost from acquiring operating inputs especially feed. The operations in the East Coast region was almost unprofitable for the reason that feed conversion rate is more than 2 resulting in higher production cost. But the other three regions indicate positive returns based on the estimated input-output ratios of 1:1.09, 1:1.17 and 1: 1.23 for Northern, Southern and Central regions, respectively. The study advocates for both managerial and policy measures that will help cut the cost of production to attract more investors and increase export.